Analysis of The Effect of Price and Promotion on Purchase Intention of Yarn with Perceived Quality as a Moderating Variable at PT. Hoja Indonesia - M. Rudi Zafa; Zulkifli Rangkuti; Irawan R D Budianto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the influence of price and promotion on purchase intention of thread products at PT. Hoja Indonesia, with Perceived Quality as a moderating variable. The textile industry, particularly thread manufacturing, is vital for supporting downstream industries, and understanding consumer behavior is essential for maintaining competitiveness. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) and SmartPLS 4 software, this study employed saturated sampling with 40 respondents, including customers and business partners purchasing thread products from PT. Hoja Indonesia. Both the measurement and structural models were analyzed to assess relationships among price, promotion, perceived quality, and purchase intention. Results indicate that price has a positive but statistically insignificant effect on purchase intention, while price significantly influences perceived quality. Promotion significantly impacts purchase intention but does not affect perceived quality. Perceived quality itself significantly affects purchase intention, highlighting its critical role in shaping consumer behavior. Moderation analysis reveals that perceived quality’s interaction with price and promotion influences purchase intention, though not significantly. These findings suggest that while perceived quality is crucial, its moderating role is limited. Companies should implement integrated marketing strategies that enhance promotional activities and strengthen consumers’ perceptions of product quality. This study contributes to consumer perception-based marketing strategies in the textile sector, particularly for thread products.